(untitled) (Canadian Medical Education Journal, 2025)
Introduction: In order to improve equity amongst leadership roles for all genders, it is important for health professions educators to better understand the intersection of gender and leadership. This study aimed to understand how gender affects leaders in health sciences and their engagement in developing themselves further within their career by exploring: 1) Their engagement with continuing professional development; 2) Their motivations for continued learning 3) The benefits/consequences of their careers. Methods: A Constructivist Grounded Theory approach was used to investigate this domain. Eligible leaders in health sciences were invited for one-on-one virtual interviews that were transcribed and analyzed by our research team. The data were examined initially in a constant comparative method with reflexive journaling and subsequently examined through axial coding for further themes. Results: Eighteen qualitative interviews were analyzed. Themes pertaining to support systems, sponsorship/mentorship, and a lack of discourse surrounding gendered constraints were identified at the intersection between gender, academic leadership, and CPD within healthcare education. Conclusion: Our findings provide insight on the gender gap and its implications on healthcare leaders’ motivations in their role, as well as engagement in continuing professional development.